IMPROVING E-LEARNING ENVIRONMENT IN TEACHING INDONESIAN AS A FOREIGN LANGUAGE - Nugraha, Setya Tri; Suwandi, Sarwiji; Nurkamto, Joko; Saddhono, Kundharu (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
This article explored e-learning environment in teaching Indonesian as a foreign language (TIFL) context. This study utilised a mixed method for data collection, including interviews and observations. There were six teachers, one IT staff member, and three curriculum developers involved in the interview. Observations were conducted with the teachers to identify their instructional activities and how they used artefacts in the e-learning environment. In this study, the use of Learning Environment, Learning Process, and Learning Outcomes (LEPO) Framework is described to evaluate the quality of the e-learning environment in TILF. The results of this study indicate that e-learning programs in TIFL must be designed with an emphasis on the intercorrelation of the dimensions that build e-learning so that the learning process takes place effectively and meaningfully. One of the important factors is how to create an effective e-learning environment. E-learning environment provides contexts in which the learners work with technology, e-learning artefact, the internet, and virtual communication to improve their language skills. In such contexts, the e-learning environment also presents challenges for both learners and teachers to use information technology effectively to maintain their learning process. The institution needs to re-engineer the e-learning artefact, mainly tools and learning objects, optimally to create a sense of presence in the e-learning. In addition, curriculum developers need to redesign the concepts of e-learning environment with integrated pedagogical and technological domains/dimensions, interface design, as well as evaluation in the e-learning programs.